Hubungan literasi kesehatan dan partisipasi posyandu dengan kebutuhan informasi kesehatan seksual dan reproduksi pada remaja putri perdesaan - Widadi, Najmatul Rahmi; Khasanah, Nur; Riska, Herliana (Holistik Jurnal Kesehatan, 2026)
Background: Adolescent girls in rural areas face various reproductive health problems exacerbated by limited access to information, sexual and reproductive health literacy, and low utilization of integrated adolescent health service posts. Purpose: To analyze the relationship between sexual and reproductive health literacy and participation in integrated adolescent health service posts with sexual and reproductive health information needs among rural adolescent girls. Method: This quantitative study with a cross-sectional approach involved 37 adolescent girls who were actively attending high school and selected using purposive sampling. Sexual and reproductive health literacy was measured using the Health Literacy Measure for Adolescents (HELMA) instrument, while participation in integrated adolescent health service posts and information needs were measured nominally across seven sexual and reproductive health topics. Data were analyzed using the Likelihood Ratio and Fisher’s Exact Test (p < 0.05). Results: The majority of respondents had moderate sexual and reproductive health literacy (67.6%) and did not participate in integrated adolescent health service posts (83.8%). The highest information needs were related to reproductive hygiene (70.3%) and sexual violence and harassment (43.2%). A significant association was found between sexual and reproductive health literacy and information needs regarding contraception (p = 0.010), whereas participation in integrated adolescent health service posts was not significantly associated with any information topics (p > 0.05). Conclusion: Sexual and reproductive health literacy is associated with contraceptive information needs among rural adolescent girls, while the contribution of integrated adolescent health service posts remains suboptimal. Strengthening health literacy and optimizing the function of integrated adolescent health service posts based on adolescent girls' information needs are required to improve the fulfillment of sexual and reproductive health information in rural areas. Suggestion: Further research is recommended to involve a larger number of respondents to strengthen the generalizability of the results and explore the quality of implementation of adolescent integrated health posts and socio-cultural factors that influence adolescent sexual and reproductive health information needs.   Keywords: Adolescent Girls; Information Needs; Integrated Adolescent Health Service Posts; Rural; Sexual and Reproductive Health Literacy.   Pendahuluan: Remaja putri di wilayah perdesaan menghadapi berbagai permasalahan kesehatan reproduksi yang diperberat oleh keterbatasan akses informasi, literasi kesehatan seksual dan reproduksi, serta rendahnya pemanfaatan pos pelayanan terpadu remaja (posyandu remaja). Tujuan: Untuk menganalisis hubungan literasi kesehatan seksual dan reproduksi serta partisipasi posyandu terhadap kebutuhan informasi kesehatan seksual dan reproduksi pada remaja putri perdesaan. Metode: Penelitian kuantitatif dengan pendekatan cross-sectional ini melibatkan 37 remaja putri yang berstatus aktif bersekolah di SMA/sederajat dan dipilih menggunakan teknik purposive sampling. Literasi kesehatan seksual dan reproduksi diukur menggunakan instrumen Health Literacy Measure for Adolescents (HELMA), sedangkan partisipasi posyandu remaja dan kebutuhan informasi diukur secara nominal pada tujuh topik kesehatan seksual dan reproduksi. Analisis data menggunakan uji Likelihood Ratio dan Fisher’s Exact Test (p < 0.05). Hasil: Mayoritas responden memiliki tingkat literasi kesehatan seksual dan reproduksi sedang (67.6%) dan tidak mengikuti kegiatan posyandu remaja (83.8%). Kebutuhan informasi tertinggi terdapat pada topik kebersihan organ reproduksi (70.3%) dan kekerasan serta pelecehan seksual (43.2%). Terdapat hubungan signifikan antara literasi kesehatan seksual dan reproduksi dan kebutuhan informasi tentang alat kontrasepsi (p = 0.010), sedangkan partisipasi posyandu remaja tidak menunjukkan hubungan signifikan dengan seluruh topik kebutuhan informasi (p > 0.05). Simpulan: Literasi kesehatan seksual dan reproduksi berhubungan dengan kebutuhan informasi alat kontrasepsi pada remaja putri, namun partisipasi posyandu remaja belum berkontribusi secara optimal. Penguatan literasi kesehatan dan optimalisasi fungsi posyandu remaja berbasis kebutuhan informasi remaja putri diperlukan untuk meningkatkan pemenuhan informasi kesehatan seksual dan reproduksi di wilayah perdesaan. Saran: Penelitian selanjutnya disarankan melibatkan jumlah responden yang lebih besar guna memperkuat generalisasi hasil serta mengeksplorasi kualitas pelaksanaan posyandu remaja dan faktor sosial budaya yang memengaruhi kebutuhan informasi kesehatan seksual dan reproduksi remaja.   Kata Kunci: Kebutuhan Informasi; Literasi Kesehatan Seksual dan Reproduksi; Perdesaan; Posyandu Remaja; Remaja Putri.